Grafted Pectin with Glycidyl Methacrylate for Multi-Sites Urease Immobilization - Abd El-Ghaffar, M.A.; Hashem, M.S. (Journal of Composites and Biodegradable Polymers, 2017)
Pectin poly glycidyl methacrylate copolymer (PGMA-g-pectin) was prepared via emulsion polymerization technique, characterized and used as multi-sites enzyme immobilization system. Urease, an enzyme model in this study, was sequentially immobilized onto the prepared carrier via both the carboxyl and epoxy groups. The structure and surface morphology of the prepared copolymer, before and after immobilization, were characterized by FT-IR and SEM. Both the amount of bounded urease and its relative activity were measured. A higher activity (about 68.4%) was measured for urease bounded to PGMA-g-SA activated with 10 mg of 1-[3-(dimethylamino) propyl]-3-ethylcarbo diimide hydrochloride (EDC) at pH 5 for 3 h. The various parameters affecting the potency of urease immobilization process (e.g. activation and immobilization time, pH and the concentration of EDC and urease) were investigated. The basic characteristics (optimum pH and temperature, thermal stability, storage stability and reusability) of the immobilized enzyme were also determined. The results showed that the immobilized urease maintained its excellent performance in detecting urea in 20 measurements and retained 70 % from its original activity after 60 days of storage at 4°C.